Kerr-newman particles: Symmetries and other properties - Arcos, H. I.; Pereira, J. G. [UNESP] (World Scientific Publishing, 2007)
The Kerr-Newman (KN) solution to Einstein’s equation shows a gyromagnetic factor g = 2, typical of a Dirac spinor. This fact has prompted many attempts to consider this solution as the exterior metric for a fundamental spin 1/2 particle. In the present work, the KN solution is proposed as the exterior and interior solution for a fundamental particle, leading to a redefinition of the particle concept. By considering the extended interpretation of Hawking and Ellis, other properties like the spacetime spinorial structure, mass and charge follow from its non- trivial geometry. A crucial point of the model is the excision of the ring singularity present in the original KN solution. This excision removes non-causal regions of the solution, and is consistent with its metric structure. Although the spacetime dimension of the singularity is of the order of the particles’s Compton wavelength, which for the electron is ? = 10-11cm, the space dimension of the ring is found to vanish. In the three-dimensional space, therefore, it is a point-like object, a property that validates the concept of fundamental particle of the model.
Keywords: Kerr-Newman solution; Particle model; Spin